Wpływ pandemii COVID-19 na gospodarkę współdzielenia w Polsce - Ziobrowska, Justyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The concept of sharing resources and services is not a new phenomenon, while the development of mobile technologies and Internet communities has resulted in the exchange of resources. It is now taking on a completely different dimension as the scale is dynamically increasing, including new sectors of management. Looking through the prism of the economic crisis, pandemic and financial problems in Polish homes being greater than before, the rational consumption turned out to be an important feature of sharing. The purpose of this article is to review the positive and negative impacts of the pandemic on selected sharing initiatives in Poland.The article is for reference only and was based on research of documents and literature.
Keywords: collaborative consumption; pandemic; sharing economy